Pediatric unilateral sensorineural hearing loss: implications and management. Issue 6 (December 2016) - Dornhoffer, James R.; Dornhoffer, John L.
Abstract : Purpose of review: The purpose of this review is to summarize current studies detailing the impact of unilateral sensorineural hearing loss in children and the most current modalities of treatment used in its management. Recent findings: Current studies corroborate historic views on the impact of unilateral sensorineural hearing loss on patient wellbeing and academic success and stress the use of additional surveillance and studies to diagnose those patients that may pass standard screening practices and suffer from lack of prompt and proper care. With respect to management, notable findings include the continuous development of improved conventional and contralateral routing of signal amplification devices that may act to provide alternatives to percutaneous bone-anchored hearing aid implantation. These include improvements in more conventional hearing aid technology, so as to bridge the performance gap with the classical bone-anchored hearing aid implant, and the development of partially implanted transcutaneous bone conduction hearing devices. Due to dissatisfaction with sound localization, a new and significant development is the burgeoning accumulation of research on cochlear implantation for the treatment of unilateral sensorineural hearing loss in children. Summary: With advances in technology in historic modalities of treatment, and the advent of new modalities such as cochlear implantation, the clinician has a wide armamentarium by which to provide treatment to patients based on clinical circumstances and patient desires.